Strategi Rekrutmen Dan Seleksi Tenaga Pendidik Dan Kependidikan Di SMP Al Ma’soem Jatinangor Sumedang - Dadang Supriyanto; Dadan Hidayatullah (CV. Alim's Publishing, 2024)
This research aims to determine the planning, organization and strategy for recruitment and selection of teaching and educational staff at Al Ma'soem Middle School, Jatingor, Sumedang Regency. This research uses qualitative methods, this research was carried out at Al Ma'soem Middle School, Jatinangor, Sumedang Regency, the techniques used in collecting data were interviews, observation and documentation. Carry out data reduction, present data, and draw conclusions as data analysis techniques for this research. The results and conclusions of this research are; 1) The teacher recruitment and selection process at Al Ma'soem Jatinangor Middle School starts with analyzing the needs of available teaching and education staff and the condition of the number of students in the current year and those estimated for the following year, then submitting it to the foundation. 2) The role of the foundation in implementing recruitment and selection is to be the party that provides human resources, which are then given to schools for selection. 3) The types of selection carried out are: administrative selection, psychological tests, written tests, micro teaching tests and interviews. 4) There is a division of work between teachers, curriculum assistants and school principals in carrying out the selection.